Observational experiment of the Antarctic ozone hole of 1991 under the Polar Patrol Baloon (PPB) Project: (2) A preliminary result of ozone and aerosol observation (abstract) - Hayashi, Masahiko; Murata, Isao; Iwasaka, Yasu-nobu; Kondo, Yutaka; Kanzawa, Hiroshi (National Institute of Polar Research, 1993)
P(論文) Among Polar Patrol Balloon (PPB) experiments, a balloon for observation of ozone and aerosol was launched from Syowa Station (69 departmental bulletin paper